Prediksi Penjualan Dan Pengendalian Persediaan Tabung Gas LPG 3 Kg Menggunakan Metode Dekomposisi Dan Model Persediaan P (Studi Kasus : Pangkalan Gas Lpg Karanggan) - Eman Lesmana; Elis Hertini; Salsabila Daradeyana (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
This paper discusses the prediction of sales and supply of 3 kg LPG gas at the Karanggan LPG base. This base needs the right policies to meet uncertain demand. Decomposition forecasting method is used to determine the prediction of sales of 3 kg LPG gas cylinders in the next period. Uncertain demand causes the inventory system to be probabilistic, so the inventory model P is used to manage the supply of 3 kg LPG cylinders with lost sales cases to obtain optimal time between orders and the total cost of inventory. Based on the research results, it is obtained forecasting results that increase every month until August 2020 and decrease in September and October 2020. The company must place LPG gas orders within 1 day intervals between orders. The total cost of selling 3 kg LPG gas using the inventory model with lost sales cases is IDR 44,122,831